FRI0479 TRENDS IN LOW TRAUMA DISTAL FOREARM FRACTURE INCIDENCE IN WOMEN AND MEN OVER 1995-2015 IN OLMSTED COUNTY, MINNESOTA, USA. (June 2019) - Bekele, Delamo; Atkinson, Elizabeth; Amin, Shreyasee
Abstract : Background: It is unclear how recent practice changes of decreased use of hormone replacement therapy and drug holidays from bisphosphonate therapy have impacted incidence of fragility fractures. Fragility (low trauma) fractures at the distal forearm in women may be more likely to be impacted by these changes as compared with men. Objectives: We examined the trends in distal forearm fracture incidence over 1995-2015, in both women and men, from Olmsted County, Minnesota, USA. Methods: Using the Rochester Epidemiology Project, a unique medical records linkage system that allows access to all (inpatient and outpatient) community medical records for Olmsted County residents, we identified all incident distal forearm fractures among residents age ≥18 years between 1995-2015. Available medical records were reviewed by trained nurse abstractors to validate distal forearm fractures identified and to determine their antecedent cause (pathological process [e.g., malignancy], severe trauma [e.g., motor vehicle accidents, sports/other recreational activities] and low trauma [by convention, equivalent to a fall from standing height or less]). Overall incidence rates were summarized separately for women and men, as well as by 5 year strata for different age groups (ages 18-39, 40-59, 60-79 and ≥ 80 yrs). Rates for women and men were each directly age-adjusted to the population distribution of US whites in 2010. Results: Between 1995-2015, we identified 2727 distal forearm fractures in women (70%, median age 62 yrs; 1915 due to low trauma) and 1193 distal forearm fractures in men (30%, median age 48 yrs; 450 due to low trauma), 92.3% of which were in whites. The overall age-adjusted annual incidence of first distal forearm fracture over 1995-2015 was 233 per 100, 000 person-years (p-y) for women and 113 per 100, 000 p-y for men. When considering only fractures due to low trauma, the overall age-adjusted annual incidence of first distal forearm fracture over 1995-2015 was 169 per 100, 000 p-y for women and 49 per 100, 000 p-y for men. Rates of low trauma distal forearm fracture appear to be stable in younger (18-39 yrs) women, but since 2005, seem to be increasing in women age 40-59 yrs (Table). In contrast, rates in older women appear to be decreasing or are stable since 2005. In men, the rates of low trauma distal forearm fracture have been relatively unchanged over the past 20 years, except in men age ≥ 80 yrs where the rates have generally been lower since 2005 (Table). Conclusion: The trend for increasing low trauma distal forearm fractures in women age 40-59 yrs may reflect the decreased use of hormone replacement therapy, which would likely have particularly impacted this age group. The decrease in fractures in men age ≥ 80 yrs may reflect greater recognition, in recent years, of osteoporosis in older men and initiation of treatment. Whether changes in practice patterns are actually contributing to these observed trends warrants further review. References: None Disclosure of Interests: None declared